Equilibrium state and sensitivity of the simulated middle-to-late Eocene climate - Baatsen, Michiel; Heydt, Anna S.; Huber, Matthew; Kliphuis, Michael A.; Bijl, Peter K.; Sluijs, Appy; Dijkstra, Henk A. (2018)
While the early Eocene has been considered in many modelling studies, detailed simulations of the middle and late Eocene climate are currently scarce. To understand Antarctic glaciation at the Eocene-Oligocene Transition (~ 34 Ma) as well as middle Eocene warmth, it is vital to have an adequate reconstruction of the middle-to-late Eocene climate. Here, we present a set of high resolution coupled climate simulations using the Community Earth System Model (CESM) version 1. Two middle-to-late Eocene cases are considered with new detailed 38 Ma geographical boundary conditions with a different radiative forcing. With 4 × pre-industrial concentrations of CO 2 (i.e. 1120 ppm) and CH 4 (~ 2700 ppb), the equilibrium sea surface temperatures correspond well to available late middle Eocene (42–38 Ma) proxies. Being generally cooler, the simulated climate with 2 × pre-industrial values is a good analog for that of the late Eocene (38–34 Ma). Deep water formation occurs in the South Pacific Ocean, while the North Atlantic is strongly stratified and virtually stagnant. A shallow and weak circumpolar current is present in the Southern Ocean with only minor effects on southward oceanic heat transport within wind-driven gyres. Terrestrial temperature proxies, although limited in coverage, also indicate that the results presented here are realistic. The reconstructed 38 Ma climate has a reduced equator-to-pole temperature gradient and a more symmetric meridional heat distribution compared to the pre-industrial reference. Climate sensitivity is similar (~ 0.7 °C/Wm 2 ) to that of the present-day climate (~ 0.8 °C/Wm 2 3 °C per CO 2 doubling), with significant polar amplification despite very limited sea ice and snow cover. High latitudes are mainly kept warm by albedo and cloud feedbacks in combination with global changes in geography and the absence of polar ice sheets. The integrated effect of geography, vegetation and ice accounts for a 6–7 °C offset between pre-industrial and 38 Ma Eocene boundary conditions. These 38 Ma simulations effectively show that a realistic middle-to-late Eocene climate can be reconstructed without the need for greenhouse gas concentrations much higher than proxy estimates. The general circulation and radiative budget allow for mild high-latitude regions and little to no snow and ice cover, without making equatorial regions extremely warm.